Virtual prediction of purple rice ferulic acid as anti-inflammatory of TNF-α signaling - Ernanin Dyah Wijayanti; Anna Safitri; Dian Siswanto; Fatchiyah Fatchiyah (The East Java Biological Society, 2022)
Purple rice is one of the main sources of ferulic acid (FA). Some studies reported anti-inflammatory properties of FA, but the interaction of FA with TNF-α signaling has not been elucidated. TNF-α is a target for anti-inflammatory drug research due to its major role in the inflammatory process. This study aims to investigate the interaction of FA with TNF-α and TNF-α receptor (TNFR) through in silico study and evaluate the drug-like properties and biological activity of FA. The interactions among FA (CID 445858), TNF-α (2AZ5), and TNFR (1NCF) were docked by Hex 8.0.0 Cuda, then visualized by Discovery Studio 2020 and LigPlot V.1.4.5. Apigenin-7-glucuronide (AG, CID 5319484) was used as the positive control. The drug-like properties were predicted by Lipinski’s rule of five and the biological activity was analyzed by PASS online. FA showed good properties as a drug-like molecule and biological activity as an anti-inflammatory. FA also showed good interaction with TNF-α and TNFR. FA bound to TNF-α at Asn92(B), Val91(B), Leu93(B), Phe124(B), Phe124(D), and Leu93(D) residues with docking energy of -214.6 kJ/mol, and bound to TNFR at Pro16(A), Glu56(B), Cys55(B), Glu54(B) residues with docking energy of -191.1 kJ/mol. FA could inhibit TNF-α – TNFR interaction by binding to TNFR at Glu54 residue, the same inhibition mechanism to AG which bind to TNFR at Glu54 and Val90. The current study shows that FA has the potential as an anti-inflammatory of TNF-α signaling and can be developed as an oral anti-inflammatory drug candidate.